Comparative analysis of the oral microbiome of burning mouth syndrome patients. Issue 1 (31st December 2022) - Lee, Byeong-Min; Park, Ji Woon; Jo, Jung Hwan; Oh, Bumjo; Chung, Gehoon
ABSTRACT: Burning mouth syndrome (BMS) is a chronic pain condition accompanied by unpleasant burning sensations of the oral mucosa. While multiple factors were proposed for the etiology, evidence suggested a neuropathic pain origin while others suspected the use of antibiotics as the underlying cause. Interestingly, several reports demonstrated the intimate interaction of the nervous system and the microbiome. The current study aims to elucidate the correlation of the oral microbiome with the pathophysiology of the primary BMS. Microbiome samples obtained from the unstimulated whole saliva of 19 primary BMS patients and 22 healthy controls were sequenced and analyzed of the V3-V4 region of 16S rRNA gene. There was a distinct difference in the microbial composition between the BMS and the control groups at all taxonomic levels. Alpha diversity indexes of the oral microbiome were significantly lower in the BMS group. The samples were readily distinguished by multidimensional scaling analysis and linear discriminant analysis effect size. Streptococcus, Rothia, Bergeyella, and Granulicatella genus were dominant in the BMS group, while Prevotella, Haemophilus, Fusobacterium, Campylobacter, and Allorevotella genus were more abundant in the healthy group. Distinct microbiome signatures of BMS patients suggested a diagnostic value and a potential role in the pathogenesis of BMS.